2010
DOI: 10.1111/j.1600-0404.2010.01435.x
|View full text |Cite
|
Sign up to set email alerts
|

Changes in CSF acetyl- and butyrylcholinesterase activity after long-term treatment with AChE inhibitors in Alzheimer’s disease

Abstract: AChEIs differently influence the activity of target enzymes in CSF independent of their pharmacodynamic effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
22
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 36 publications
4
22
0
Order By: Relevance
“…This relationship is perhaps counter-intuitive, given that the goal of ChE-I treatment is to dampen AChE activity and thus enhance cholinergic transmission. However, our results are consistent with previous studies which reported increased AChE activity in plasma and CSF among AD patients who were treated with donepezil (22, 46-48). It is possible that suppression of ChE activity in AD patients is transient, and that treatment may lead to a “rebound” of activity via compensatory mechanisms (49), perhaps explaining the apparently transient benefit of ChE-I treatment (50).…”
Section: Discussionsupporting
confidence: 93%
“…This relationship is perhaps counter-intuitive, given that the goal of ChE-I treatment is to dampen AChE activity and thus enhance cholinergic transmission. However, our results are consistent with previous studies which reported increased AChE activity in plasma and CSF among AD patients who were treated with donepezil (22, 46-48). It is possible that suppression of ChE activity in AD patients is transient, and that treatment may lead to a “rebound” of activity via compensatory mechanisms (49), perhaps explaining the apparently transient benefit of ChE-I treatment (50).…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, a 13-week, randomized, open-label study56 in patients with mild-to-moderate AD showed that rivastigmine significantly decreased activity of both AChE and BuChE in the CSF by 42.6% ( P <0.001 vs baseline; AChE protein levels decreased by 21.8%) and 45.4% ( P <0.001 vs baseline; BuChE protein levels decreased by 9.3%), respectively, whereas donepezil and galantamine did not significantly decrease BuChE activity, and these enzymes were associated with increased levels of cholinesterases in the CSF. Similarly, results from a clinical study57 in patients with probable AD showed that rivastigmine treatment decreased CSF AChE and BuChE activity and was statistically significant in only rivastigmine 12 mg/day group ( P <0.01) as there were fewer patients in the 6 and 9 mg/day groups; however, treatment with donepezil ( P <0.0001) and galantamine ( P <0.001) showed significant increase in CSF AChE activity, but no change in BuChE activity was observed. The change in CSF AChE activity with donepezil treatment was dose related (mean percentage change with 5 and 10 mg/day: +88% and +116%, respectively), and the percentage change in CSF AChE activity was significantly different between the two doses ( P <0.01), whereas the change in CSF AChE activity with galantamine was not dose related (8 and 12 mg/day: +53% and +52%, respectively).…”
Section: Rivastigmine: Dual Inhibitor Ache/buchementioning
confidence: 94%
“…CSF concentrations of PTH were below the lower detection limit of the assay (3 ng/L). CSF AChE and BuChE activities were determined using in house assays as previously described in detail [25]. …”
Section: Methodsmentioning
confidence: 99%